Effect of Egg Yolk Type on the Quality of Post-Thawing Goat Semen After Resiquimod-Based Sexing - Yulio, Ivan; Solihati, Nurcholidah; Widyastuti, Rini (Faculty of Animal Husbandry, Universitas Padjadjaran, 2026)
Egg yolk is an important component of semen extenders that functions to maintain spermatozoa quality during cryopreservation. This study aimed to analyze the effect of different egg yolk types in a Tris extender on the abnormality and recovery rate of post-thawing goat spermatozoa following resiquimod-based sexing. The study was conducted as a laboratory experiment using a completely randomized design with four egg yolk type treatments: commercial chicken egg yolk (P1), native chicken egg yolk (P2), quail egg yolk (P3), and duck egg yolk (P4). Fresh Sapera goat semen was processed using a resiquimod-based swim-up method and subsequently cryopreserved in a Tris extender containing each egg yolk type. The observed parameters included spermatozoa abnormality and recovery rate in the upper and lower layers after thawing. Data were analyzed using ANOVA followed by Duncan’s multiple range test. The results showed that spermatozoa abnormalities ranged from 0.60–1.40% in the upper layer and 0.60–1.10% in the lower layer, with no significant differences among treatments. In contrast, egg yolk type significantly affected the recovery rate. The highest average recovery rate was obtained with commercial chicken egg yolk (42.56%), followed by native chicken (40.37%), duck (39.97%), and quail egg yolk (31.97%). It was concluded that commercial chicken egg yolk was the best egg yolk type for maintaining the recovery rate of post-thawing goat spermatozoa following resiquimod-based sexing.